LINGUISTICS AND HUMANITIES STUDY - Mahsun Mahsun (LITERASI: Indonesian Journal of Humanities, 2011)
Language is not merely one of cultural elements, but also medium of culture itself. As medium of culture, we can study cultural systems and behaviors of its members. This article offers conceptual and methodological formula about contribution of linguistics in reading cultural systems and behaviors of particular language speakers. By using Sumbawa and Sasak language as data, I will elaborate language units in both of them from which some cultural behaviors appear. Keywords: information, culture, humanism, linguistic,